2021
DOI: 10.1002/essoar.10506322.2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tropical free-tropospheric humidity differences and their effect on the clear-sky radiation budget in global strom-resolving models

Abstract: Free-tropospheric water vapor strongly impacts the Earth's outgoing longwave radiation (OLR) and therefore plays a key role in controlling the clear-sky response of the climate system to an increase in greenhouse gases. It is now widely accepted that this response is described by a warming and moistening of the atmosphere that is implied if the relative humidity (RH) and lapse rate were to depend on temperature alone, which corresponds to a warming at approximately constant RH (e.g., Held & Soden, 2000;Po-Ched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…In the following we focus on R differences in the mid troposphere (4 km to 8 km, indicated by the gray lines in Figure 1). Although mid-tropospheric R differences are, similar as in the DYAMOND ensemble, not particularly large, Lang et al (2021) showed that R differences in this region are particularly important for differences in OLR.…”
Section: Sensitivity Experimentsmentioning
confidence: 72%
See 4 more Smart Citations
“…In the following we focus on R differences in the mid troposphere (4 km to 8 km, indicated by the gray lines in Figure 1). Although mid-tropospheric R differences are, similar as in the DYAMOND ensemble, not particularly large, Lang et al (2021) showed that R differences in this region are particularly important for differences in OLR.…”
Section: Sensitivity Experimentsmentioning
confidence: 72%
“…Comparably large R changes occur in the TTE and 2-mom experiments, in which the parameterizations of turbulence and microphysics were changed. The largest changes occur in the lower and mid troposphere, where they have a larger impact on the clearsky OLR than those in the upper troposphere (Lang et al, 2021). Changing to the TTE turbulence scheme results in a strong increase in R of up to 8% over a broad altitude layer between 2 km to 6 km.…”
Section: Sensitivity Experimentsmentioning
confidence: 98%
See 3 more Smart Citations